Implementasi Telenursing dalam Manajemen Bencana - Soni Roy Kurniawan Hulu; Rr. Tutik Sri Hariyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This literature review aims to identify the implementation of telenursing in disaster management. This study uses the literature review method, using the ProQuest, PubMed, ScienceDirect, Sage Journals, and Scopus databases. The search results obtained 182 journals after further analysis. They got six articles that were reviewed with criteria discussing the topic of using information systems in disaster management, telenursing in disaster management, and the role of nurses in disaster management. The results of this literature divide four main topics: the benefits of telenursing in disaster management, the implementation of telenursing, the challenges in implementing telenursing, and the results of implementing telenursing in disaster management. In conclusion, telenursing is a practical step in reaching disaster victims to get fast health care and make patients independent. Keywords: Nursing Care, Nurse Disaster Management, Telenursing